Delayed Diagnosis of an Eating Disorder in a Male Patient With Superior Mesenteric Artery Syndrome: Results From a Case Study - Recio-Barbero, María; Fuertes-Soriano, Sara; Cabezas-Garduño, Janire; López-Atanes, Mayte; Peña-Rotella, Alvar; Sáenz-Herrero, Margarita (Frontiers in Psychiatry, 2019)
Background: Eating Disorders (EDs) are serious and life-threatening mental diseases characterized by abnormal or altered eating habits. The prevalence is variable, being influenced by diverse sociocultural factors. Historically, the prevalence of EDs has been higher in women (90%), although the incidence of these disorders in men appears to be increasing. In daily medical practice, when considering the presentation of other medical complications associated to the development of an ED, few is known about its real prevalence in men. Among them, some severe gastrointestinal complications that are rarely presented, such as the Superior Mesenteric Artery Syndrome (SMAS), can produce life-threatening results. Despite that, very few cases of men presenting this pathology are reported in literature. Case presentation: A 38-year-old male without a history of psychiatric disease was admitted to the Emergency Department with nausea, abdominal pain and severe malnutrition (BMI 15.7). He was diagnosed with SMAS and was studied by multiple specialists on suspicion of a probable organic origin of his thinning. The suspected diagnosis of ED was rejected for months by some professionals, as well as by the patient and his family, until it was finally diagnosed with Unspecified Feeding and Eating Disorder (USFED). Conclusion: This case represents an example of diagnostic challenge where a delayed diagnostic of an ED in a male patient was made probably due to gender bias in clinical research and practice. There is described in the literature numerous reports of women diagnosed with SMAS with a previous diagnosis of an ED; however, few cases were found in men. In this clinical case the patient suffered a significant diagnostic delay, probably due to the lack of diagnostic suspicion given by the differences in the prevalence and clinical presentation of EDs in women and men.